Severe Lactic Acidosis in a Patient with B-Cell Lymphoma: A Case Report and Review of the Literature - Farn Huei Chan; Daniel Carl; Laurel J. Lyckholm (Case Reports in Medicine)
Lactic acidosis is commonly observed in clinical situations such as shock and sepsis, as a result of tissue hypoperfusion and hypoxia. Lymphoma and leukemia are among other clinical situations where lactic acidosis has been reported. We present a case of a 59-year-old female with lactic acidosis who was found to have aggressive B-cell lymphoma. There have been 29 cases of lymphoma induced lactic acidosis reported thus far; however all reported cases have abnormal vital signs or concomitant medical conditions that may lead to lactic acidosis. The pathogenesis of malignancy-induced lactic acidosis is not well understood; however associated factors include increased glycolysis, increased lactate production by cancer cells, and decreased hepatic clearance of lactate. When it occurs, lactic acidosis is a poor prognostic sign in these patients. Prompt diagnosis and treatment of underlying lymphoma or leukemia remains the only way to achieve complete resolution of lactic acidosis in these patients.